Metabolic Variations, Antioxidant Potential, and Antiviral Activity of Different Extracts of Eugenia singampattiana (an Endangered Medicinal Plant Used by Kani Tribals, Tamil Nadu, India) Leaf. (15th July 2014) - John, K. M. Maria; Ayyanar, Muniappan; Jeeva, Subbiah; Suresh, Murugesan; Enkhtaivan, Gansukh; Kim, Doo Hwan
Abstract : Eugenia singampattiana is an endangered medicinal plant used by the Kani tribals of South India. The plant had been studied for its antioxidant, antitumor, antihyperlipidemic, and antidiabetic activity. But its primary and secondary metabolites profile and its antiviral properties were unknown, and so this study sought to identify this aspect in Eugenia singampattiana plant through different extraction methods along with their activities against porcine reproductive and respiratory syndrome virus (PRRSV). The GC-MS analysis revealed that 11 primary metabolites showed significant variations among the extracts. Except for fructose all other metabolites were high with water extract. Among 12 secondary metabolites showing variations, the levels of 4-hydroxy benzoic acid, caffeic acid, rutin, ferulic acid, coumaric acid, epigallocatechin gallate, quercetin, myricetin, and kaempferol were high with methanol extract. Since the flavonoid content of methanol extracts was high, the antioxidant potential, such as ABTS, and phosphomolybdenum activity increased. The plants antiviral activity against PRRSV was for the first time confirmed and the results revealed that methanol 25 µ g and 75 to 100 µ g in case of water extracts revealed antiviral activity.